Factors Affecting Milk Consumption Among School Children In Urban And Rural Areas Of Selangor, Malaysia - Hendijani, Roozbeh Babolian (2009)

(untitled)
Consumers who are getting more health conscious have encouraged the growth of healthy foods consumption in the Malaysia's market. One of the products that have been always closely related to healthy food is milk. Milk is being sold from hypermarkets to mini market in the country and it means that this product is getting familiar among Malaysians. However, the consumption of milk is still low. Therefore, the main purpose of this study was to investigate the present beverage choice of school children and the other objectives of this study were to examine the most preferred flavor of milk that is available in the market and determine the effect of personal and environmental factors that influenced children's intention to consume milk. Knowing about the factors which affect on children’s intention will help marketers in profiling the children based on the factors which encourage them to consume milk. Understanding the factors that will influence children to drink milk is important in order to increase the consumption of this product. The study investigated eight factors that could influence children milk consumption. The eight factors investigated were attitude to sensory properties, belief to health benefits, packaging, consumption patterns, effect of family members, effect of friends, availability and advertising. A total of 400 students of 11 years old primary school children were chosen for this study. Several schools in different towns from urban and rural areas of Selangor were selected. Of the 400 students surveyed, 389 questionnaires were usable. Multiple linear regression, and cross-tabulation were used to analyze the factors affecting the intention to consume milk. This study found that the preferred beverages of children were: drinking water, Milo, fruit juice, milk, yoghurt drink, Ribena, tea and soft drinks. Among different types of milk, children preferred flavored milk rather than plain milk. From the results of this research, personal factors were more influential than environmental factors. Additionally, packaging and advertising had less effect on children's intention to consume milk. To increase milk intake among children, marketers need to focus and strengthen the acceptability of milk and increase consumption by altering perception of milk advertisements. This study gives new insights on children's perception. It provides the profile of children who are likely to drink milk based on personal and environmental factors in different living areas. Key words: Intention to consume, Social environment, Physical environment, milk consumption, primary school children